Design for invention: a framework for identifying emerging design–prior art conflict. (3rd October 2018) - Jiang, Pingfei; Atherton, Mark; Sorce, Salvatore; Harrison, David; Malizia, Alessio
ABSTRACT: The increasing complexity of patented mechanical designs means that their novelty and inventive steps increasingly rely on interacting geometric features and how they contribute to device functions. These features and interactions are normally incorporated in patents through clear patent claims. However, patents can be difficult to interpret and understand for designers due to their legal terminologies. This suggests there is a need for greater awareness of relevant prior art amongst designers in terms of avoiding potential conflict. This paper presents a framework that helps designers obtain insight on relevant prior art and enables emerging design–prior art comparison. The framework mainly contains development of a patent graphical functional representation, a domain-specific ontology and a semantic database. The graphical representation presenting the functional reasoning of patents in terms of interacting geometric features. A domain-specific ontology enables knowledge sharing and conceptualisation, providing a standardised vocabulary for describing patented designs. By formulating patent data into a semantic database, commonality of working principles between an emerging design and prior art can be identified. This enables early identification of potential conflict and thereby could help designers steer their emerging designs away from protected solutions. A computer tool being developed based on this approach is also described.